The characterization of the complete chloroplast genome of wild Elymus nutans. Issue 1 (2nd January 2019) - Yang, Chao; Wu, Xiaoyun; Guo, Xian; Bao, Pengjia; Chu, Min; Zhou, Xuelan; Liang, Zeyi; Ding, Xuezhi; Yan, Ping
Abstract: Elymus nutans is an alpine plant, which plays an important role in maintaining ecological system and the development of animal husbandry in the Tibetan region of China. However, the population of wild E. nutans notably decreased in recent years with overgrazing and ecological environment deterioration, and the germplasm resources have been threatened. This study reported a complete circular chloroplast genome of E. nutans, which was 134, 147 bp in length, containing a pair of inverted repeats (IRs) of 10, 541 bp separated by one small single copy (SSC) region of 14, 036 bp and one large single copy (LSC) region of 99, 029 bp. A total of 123 genes, including 87 protein-coding genes, 32 transfer RNA genes and four ribosomal RNA genes were predicted from the chloroplast genomes. The overall GC content of the chloroplast genome was 38.34% and the corresponding values of the IR, SSC and LSC were 48.7%, 32.4% and 37.0%, respectively. The results of phylogenetic analysis showed that wild E. nutans was clustered closely with Triticum aestivum .